Persepsi Dukungan Organisasi dan Kinerja Karyawan di Indonesia: Studi Metaanalisis - Rahmawati, Septi Nuzulia; Zulaifah, Emi; Akmala, Lifthya Ahadiati (Universitas Islam Indonesia, 2022)
Research and development of organizational performance theory has been done since the 1950s and it is found that one of the important factors that determine the performance of employees is the perception of organizational support. Performance refers to the extent of the contribution given by the employees to an organization; meanwhile, the perception of organizational support is an individual assessment on the availability of help from organization to support the duty implementation to make it run effectively and to help the individuals in facing any stressful situations. This study examined the consistency of the correlation between the perception of organizational support and employee performance by correcting the sampling errors using the meta-analysis technique. The quantitative review used 26 studies obtained by accessing online articles with inclusion criteria (1) primary study with the independent variable is perception of organizational support or organizational support and the dependent variable is employee performance with a time span of 2010-2020 (2) containing statistical values of N, r, t or F (4) samples are employees in Indonesia.The exclusion criteria imposed included: (1) the year of the articles should be before 2010 (2) Access for full articles were not available so that tracing the method used in the study was not possible (3) Methodological weakness was identified which become the reason why the research result was not significant. The results of the meta-analysis study with a sample of 2,460 respondents showed that perceived organizational support was positively and significantly correlated with employees’ performance with a correlation coefficient of .364 and with the confidence level of 95%.